Vascular neuropeptide Y contributes to atherosclerotic plaque progression and perivascular mast cell activation - Lagraauw, H. Maxime; Westra, Marijke M.; Bot, Martine; Wezel, Anouk; van Santbrink, Peter J.; Pasterkamp, Gerard; Biessen, Erik A.L.; Kuiper, Johan; Bot, Ilze (Atherosclerosis, 2014)
Neuropeptide Y is an abundantly expressed neurotransmitter capable of modulating both immune and metabolic responses related to the development of atherosclerosis. NPY receptors are expressed by a number of vascular wall cell types, among which mast cells. However, the direct effects of NPY on atherosclerotic plaque development and progression remain to be investigated. In this study we thus aimed to determine whether NPY is expressed in atherosclerotic plaques and to establish its role in atherosclerotic plaque development. NPY expression was seen to be increased up to 2-fold in unstable human endarterectomy plaques, as compared to stable plaques, and to be significantly upregulated during lesion progression in apoE−/− mice. In apoE−/− mice focal overexpression of NPY in the carotid artery significantly increased atherosclerotic plaque size compared to controls, while plaque composition was unaffected. Interestingly, perivascular mast cell activation was significantly higher in the NPY-overexpressing mice, suggesting that NPY may impact plaque progression in part via mast cell activation. Furthermore, in vitro NPY-induced murine mast cell activation resulted in the release of pro-atherogenic mediators including IL-6 and tryptase. Our data show that NPY expression is increased during atherogenesis and in particular in unstable plaques. Furthermore, perivascular overexpression of NPY promoted plaque development and perivascular mast cell activation, suggestive of a role for NPY-induced mast cell activation in lesion progression. •Neuropeptide Y is increased in advanced and unstable atherosclerotic lesions.•Local NPY overexpression in apoE−/− mice increased lesion progression.•NPY overexpression resulted in increased perivascular mast cell degranulation.•Stimulation of mast cells with NPY resulted in pro-inflammatory mediator release.•NPY-induced mast cell activation may contribute to the pro-atherogenic effect of NPY.